2008
DOI: 10.1117/12.776532
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber grating-based sensing system for use in pavement health monitoring

Abstract: In this paper, we describe the development and realization of a sensing system using a high-resolution temperature and strain sensor with fiber Bragg grating (FBG) technology and a simple and low-cost long-period grating (LPG) sensor for the water level measurement in pavement structures. The FBG sensor consists of a reference fiber grating and a grating pair scheme that could offer the potential of simultaneous measurement of strain and temperature for monitoring pavement structures. For FBG sensor, experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Experimental results of FBG sensor used have shown that measurement errors of 6 micro strains and 0.13 Celsius for strain and temperature could be achieved, respectively [12].…”
Section: Shm Technologies For Pavement and Bridge Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results of FBG sensor used have shown that measurement errors of 6 micro strains and 0.13 Celsius for strain and temperature could be achieved, respectively [12].…”
Section: Shm Technologies For Pavement and Bridge Structuresmentioning
confidence: 99%
“…By introducing innovative FOS in a real-time pavement and bridge monitoring system physical parameters, such as strain, temperature and water level condition, can be obtained for the required section in long term [12]. These data can aid structural evaluation, performance assessment and accurate analysis of pavement and bridge structures.…”
Section: Shm Technologies For Pavement and Bridge Structuresmentioning
confidence: 99%
“…[18][19][20][21] These technologies have shown unique advantages over conventional monitoring methods, including tiny size, high sensitivity, immunity to EMI, good durability, and the ability of multiplexing. The early-stage study on the feasibility of fiber optic sensing in pavement monitoring was introduced by Tang et al 22 Wang et al 23 and Wang and Tang 24 developed a high-resolution temperature and strain sensor using fiber Bragg grating (FBG) technology and a simple and low-cost long-period grating (LPG) sensor for measuring the water level in pavement structures. In the research of Dore et al, 25 the Fabry-Perot (F-P)-based fiber optic strain sensors were applied to monitor small strains of existing pavements.…”
Section: Introductionmentioning
confidence: 99%
“…The primary motivation of this study is to develop and evaluate a light weight and low-cost liquid-level sensor using reflective long-period fiber grating (LPFG), which has the potential for use in civil and agronomy engineering work such as ground water level monitoring for pavement structures or water level control for the increase in crop yield using deep-ponding in paddy fields [1,2]. Further, it could be used on other applications such as liquid-level monitoring of tanks or reservoirs for industrial sectors, debris flow monitoring and warnings for the tropical cyclone season, as well as water level monitoring for hydraulic applications such as pipes, channels, and dams.…”
Section: Introductionmentioning
confidence: 99%